1985
DOI: 10.1080/00268978500101761
|View full text |Cite
|
Sign up to set email alerts
|

N.M.R. study of the dynamic structure of isopropylbenzene

Abstract: The dynamic molecular behaviour of isopropylbenzene, IPB, in the liquid and supercooled state has been investigated by N.M.R. The proton, deuterium and 1~C relaxation times were measured in selectively deuterated IPB, over the temperature range 125 to 200K and the pressure range 1 bar to 5 kbar. The viscosity range extended from 1 cP to 10 P. The most significant result of the study is that although at ambient pressures the modified DebyeStokes-Einstein relation adequately describes the microscopic dynamics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The results obtained by Artaki and Jonas [308,309] are that (a) at fixed T , the parameter KV, increases with density if the molecules lack an axis of symmetry. Thus, KV, is sensitive to volume effects [308,309]; (b) at high pressure the linearity between r0 and r)/T is absent [308,309]; (c) volume plays the crucial role in the coupling of rotational and translational motions [308,309]; (d) under isochoric conditions, KV, is insensitive to changes in kinetic energy [308,309]; and (e) in the viscosity range of up to 10 P, the DSE relations adequately represent the dynamics of isopropylbenzene in the slip limit [308,309].…”
Section: E Validity Of Debye-stokes-einstein Relationsmentioning
confidence: 97%
See 2 more Smart Citations
“…The results obtained by Artaki and Jonas [308,309] are that (a) at fixed T , the parameter KV, increases with density if the molecules lack an axis of symmetry. Thus, KV, is sensitive to volume effects [308,309]; (b) at high pressure the linearity between r0 and r)/T is absent [308,309]; (c) volume plays the crucial role in the coupling of rotational and translational motions [308,309]; (d) under isochoric conditions, KV, is insensitive to changes in kinetic energy [308,309]; and (e) in the viscosity range of up to 10 P, the DSE relations adequately represent the dynamics of isopropylbenzene in the slip limit [308,309].…”
Section: E Validity Of Debye-stokes-einstein Relationsmentioning
confidence: 97%
“…This relation does not depend on the mechanism that leads to frictional dissipation [311,297], Consequently, if deviations from SE are observed experimentally, then it may be fruitful to look for additional nonviscous mechanisms for dissipation [311 , 2971. The second reason is based on the experiments of Artaki and Jones [309], which measured the pressure dependence of q and rotational relaxation time T at fixed temperature. By introducing activation volumes AK and AV,,, which depend on temperature, q and T are fitted to the functional form [309,311] T = exp P AV,IRT where p = AV,IAV,, is not a universal quantity.…”
Section: E Validity Of Debye-stokes-einstein Relationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The elucidacation of relaxation behaviour of high viscosity systems has been the topic of several studies over the years [1][2][3][4]. In particular, a considerable amount of work, both experimental and theoretical, has been devoted to studying the adequacy of the hydrodynamic Stokes-Einstein model to describe the microscopic molecular dynamics in liquid systems and in particular to elucidate the relationship between the microscopic reorientational correlation time τ and the macroscopic viscosity η of the medium [5][6][7][8][9][10][11]. In many cases the modification of the hydrodynamic model based on the concept of anisotropy of intermolecular potentials, introduced by McClung and Kivelson [12], is used.…”
Section: Introductionmentioning
confidence: 99%
“…In addition it provides information about the degree of anisotropy characterizing the motions. Jonas and co-workers examined the validity of the Debye equation over a wide range of fluidity changes, conducting an extensive study on low viscosity fluids [6,7] and on a series of highly viscosity liquid monosubstituted benzenes [8,9]. Artaki and Jonas [8] have shown that for anisotropically reorienting molecules the rotational-translational coupling parameter increases with increasing density, in contrast to molecules that posses a symmetry axis, which allows for relatively unhindered reorientation, where the coupling parameter decreases with increasing density.…”
Section: Introductionmentioning
confidence: 99%